Striving to be “normal” : exploring identity and positioning in the narratives of a migrant woman living in Finland - Pratesi, Elisa (2021)
This case study investigates the identity of an Afghan migrant woman who recently arrived in Finland, and the ways societal normative beliefs about immigration and integration in Finland are revealed in her narratives. This study considers identity from a poststructuralist and social constructivist perspective as a continuous work in progress and as articulated in interaction. Drawing on data from ethnographically informed observation and open-ended interviews carried out in the participant’s home, the present study adopts positioning as the methodological framework for the analysis. What it found was that the participant had, to some degree, internalized dominant societal normative beliefs about immigration and integration in Finland that she was exposed to in her daily life, and that these influenced her own sense of self. Specifically, learning Finnish and finding a job were viewed as the main signs of successful integration in Finland, reflecting main- stream discourses on the matter. Failing to meet these expectations, the participant of this study viewed herself as not “normal”, a notion further reinforced by her positioning herself as a struggling student in comparison to her peers in her Finnish class. However, this negative positioning at the level of the participant’s narratives was also challenged in interviews, where she would use her relationship with her audience and the space of her home as a resource to position herself in a more powerful and agentic way. The findings of this case study cannot be generalized, as it focuses the individual experiences of a single participant. Nevertheless, it hopes to provide a small “real life example” of what it means to be a migrant in integration training in Finland, paving the way for future research that could, through a larger case study with more participants, further explore the extent to which such dominant societal normative beliefs emerge in migrants’ narratives and, potentially, identify wider patterns or trends.